Evaluasi Pengelolaan Limbah B3 Dengan Konsep Reduce, Reuse, Recycle (3R) Di RSUD Jenderal Ahmad Yani Metro Tahun 2025 (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Management of hazardous and toxic waste (B3) in hospitals is an important aspect of maintaining environmental health and preventing pollution risks. RSUD Jenderal Ahmad Yani Metro has implemented hazardous waste management using the reduce, reuse, recycle (3R) concept; however, its implementation has never been comprehensively evaluated. This study aimed to evaluate the management of hazardous waste using the 3R concept at RSUD Jenderal Ahmad Yani Metro based on the Regulation of the Minister of Environment and Forestry No. P.56/Menlhk-Setjen/2015 and to identify the supporting factors. This research used a qualitative design with a case study approach. The research informants consisted of 23 participants selected using purposive sampling, including the hospital director, ward heads, IPCN, sanitation officers, 3R waste management officers, and sanitation operators. Data were collected through observation, in-depth interviews, and document review using interview guidelines and checklists. Data analysis was conducted using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results showed that the transportation, storage, and processing stages of hazardous waste management were in accordance with the Regulation of the Minister of Environment and Forestry No. P.56/Menlhk-Setjen/2015. However, the sorting and containerization processes were not fully compliant because recyclable waste was still mixed with other hazardous waste. In addition, several supporting factors were identified, including the lack of training and certification among human resources, inadequate infrastructure, and the absence of technical guidelines and standard operating procedures for the 3R waste bank. Therefore, improving human resource capacity, infrastructure, and internal hospital regulations is necessary to optimize 3R-based hazardous waste management.